Combining a Hill Encryption Algorithm and LSB Technique With Dispersed Way for Securing Arabic and English Text Messages Hidden in Cover Image - Whab Abood, Enas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper a hybrid system was designed for securing transformed or stored text messages(Arabic and english) by embedding the message in a colored image as a cover file depending on LSB (Least Significant Bit) algorithm in a dispersed way and employing Hill data encryption algorithm for encrypt message before being hidden, A key of 3x3 was used for encryption with inverse for decryption, The system scores a good result for PSNR rate ( 75-86) that differentiates according to length of message and image resolution.